Does educational tourism significantly influence economic growth? evidence from a macro-econometric modelling - Tang, Chor-Foon; Cheah, Yong Kang; Chua, Soo Y. (Universiti Malaysia Sarawak, 2019)
This study augmented the IS-LM macroeconomics model to investigate the relevance of educational tourism to economic growth in Malaysia. We utilise the vector autoregressive model with exogenous variables to examine the dynamic impact of educational tourism, interest rate, and money on economic growth over the period from 1996:Q1 to 2015:Q4. The results indicate that both money supply and educational tourism have a positive effect on economic growth, while the effect of real interest rate on economic growth is negative. The impulse response and variance decomposition also suggest that educational tourism is relevant and has a positive long-term influence on economic growth.